Analysis of advanced nuclear material attractiveness using the target nuclear material mass information - Ko, Danwoo; Jeong, Yonhong; Woo, Seung Min (Nuclear engineering and technology, 2025)
Nuclear material attractiveness assesses proliferation risks by evaluating intrinsic properties such as critical mass, heat content, dose rate, and spontaneous neutron emission. These factors vary according to the isotope ratios and composition. As a result, the FOM assesses nuclear material attractiveness qualitatively rather than from an absolute mass-based evaluation perspective. For instance, the FOM value exceeds 2 with only 1.28 kg of Pu, even though this amount is generally insufficient for strategic nuclear weapon production. To expand the FOM application, this study introduced a new mass evaluation factor using Significant Quantity (SQ), a concept used in safeguards, called FOMQ. The new factor was designed to enable attractiveness evaluation by providing information on how the quantity of the target nuclear material compares to the SQ. Calculations using MCNP and ORIGEN showed that for 7.94 kg of Pu, the FOM1Q was 0.99 (FOM1: 2.77), and at 15.6 kg, it increased to 1.28 (FOM1: 2.76). These results demonstrate that incorporating mass factors into the FOM allows for a more comprehensive proliferation risk assessment by considering both the quality and quantity of nuclear materials. This enhanced methodology provides a better framework for evaluating proliferation risks.